2020
DOI: 10.1038/s41590-020-0777-3
|View full text |Cite|
|
Sign up to set email alerts
|

A regulatory T cell Notch4–GDF15 axis licenses tissue inflammation in asthma

Abstract: Elucidating the mechanisms that sustain asthmatic inflammation is critical for precision therapies. We found that IL-6 and STAT3 transcription factor-dependent upregulation of Notch4 receptor on Iung tissue regulatory T (T reg ) cells is necessary for allergens and particulate matter pollutants to promote airway inflammation. Notch4 subverted T reg cells into T H 2 and T H 17 effector T (T eff ) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
99
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(106 citation statements)
references
References 48 publications
(44 reference statements)
4
99
1
2
Order By: Relevance
“…Interestingly, a different study linked β-catenin expression to ILT3 expression within Treg; however, this study showed that cells with lower expression of β-catenin had higher levels of ILT3 (21). This is the opposite of what we would expect given our findings and those of others (20). Moreover, to date inhibitors of β-catenin improved immune responses to different types of cancers (58).…”
Section: Discussioncontrasting
confidence: 85%
See 4 more Smart Citations
“…Interestingly, a different study linked β-catenin expression to ILT3 expression within Treg; however, this study showed that cells with lower expression of β-catenin had higher levels of ILT3 (21). This is the opposite of what we would expect given our findings and those of others (20). Moreover, to date inhibitors of β-catenin improved immune responses to different types of cancers (58).…”
Section: Discussioncontrasting
confidence: 85%
“…However, prostaglandin E2 (PGE2) also an arachidonic acid metabolite like PGI2, activated β-catenin (57). A recent study linked Wnt signaling and activation of β-catenin with the promotion of Th2 reprogramming of Treg in models of allergic disease and asthma (20). Interestingly, a different study linked β-catenin expression to ILT3 expression within Treg; however, this study showed that cells with lower expression of β-catenin had higher levels of ILT3 (21).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations